Predictors of vasovagal reactions during preoperative autologous blood donation: a single-institution analysis - Nishimori, Hisakazu; Fujii, Nobuharu; Fujii, Keiko; Ikeda, Tohru; Asano, Naomi; Ogo, Hiroaki; Yamakawa, Miwa; Takagi, Naoe; Otsuka, Fumio; Ikeda, Kazuma (International journal of hematology, 2017)
Studies examining risk factors associated with vasovagal reactions (VVRs) during autologous blood donations, especially in younger subjects, have been limited. The aim of the present study was to define risk factors for VVRs during preoperative autologous blood donation in patients, including those younger than 18 years old. We retrospectively analyzed 4192 autologous, preoperative blood donations between 2007 and 2015 at Okayama University Hospital. Eighty-seven (2.08%) of the patients experienced VVRs. VVRs occurred approximately three times as often in patients 0–17 years old (16/320, 5.0%) than in patients 18 years and older (71/3872, 1.8%). In particular, VVRs occurred more frequently in those 10–13 years old, and decreased with older age ( P = 0.006). In a univariate analysis, younger age, lower body mass index, lower systolic blood pressure, lower body weight, lower total blood volume, female gender, first-time collection, and higher heart rate were associated with a higher incidence of VVRs. In a multivariate analysis, lower systolic blood pressure ( P < 0.001), higher heart rate ( P = 0.007), and first-time collection ( P = 0.015), remained independent predictors of VVRs. These results emphasize the need for careful attention during blood collection.